The impact of tillage on the yield of maternal lines of maize hybrids - Marenych, M.; Koba, K. (Scientific Progress & Innovations, 2024)
Tillage is a crucial agronomic operation in agriculture as it affects soil properties, the environment, and crop growth. This study compares different tillage methods for the 2021–2023 crop years, including ploughing, strip tillage, and deep loosening. The options were randomly placed. The research aimed to identify methods for increasing the yield of maize hybrid maternal lines by analyzing the influence of tillage methods. The results showed that the ploughing variants with the P1/380 mother line had the highest yield at 5.24 t/ha, which is 12 % more than strip till and 5.7 % more than deep loosening when growing the same line. In ploughing variants, the yield of the mother line of the P1/380 hybrid was 12 % higher than the other two tested lines. In Strip till variants, the yield was 4–14 % higher, and in deep loosening variants, it was 8–10 % higher. The line of the mother form of the P2/340 hybrid was quite stable in all tillage options. Thus, the highest yield on average for 2021–2023 was 4.70 t/ha for ploughing, which is only 3–6 % higher than other variants of the experiment. The lowest yield was recorded for the variants of cultivation of the mother line of the P3/280 hybrid, which yielded 3.96 t/ha in variants that used Strip till technology. Upon analysis of the average yield of the mother lines, it was discovered that the highest yield was obtained from the P1/380 cultivation variants, with a yield of 4.93 t/ha. This is 0.38 t/ha more than P2/340 and 0.59 t/ha more than P3/280. The average yield by cultivation methods is 4.32 t/ha for ploughing, 4.12 t/ha for deep loosening, and the lowest yield was observed for Strip till at 3.93 t/ha. The impact of each factor was established using multivariate analysis of variance. Genetic properties had the greatest influence on the yield (54 %), followed by the method of soil cultivation (41 %). It is recommended that further research be conducted to determine the impact of weather conditions on seed crop yields and the economic efficiency of technological processes.